Quasi-classical Limit of a Spin Coupled to a Reservoir - Michele Correggi; Marco Falconi; Michele Fantechi; Marco Merkli (Quantum)
A spin (qubit) is in contact with a bosonic reservoir. The state of the reservoir contains a parameter $ε$ interpolating between quantum and classical reservoir features. We derive the explicit expression for the time-dependent reduced spin density matrix, valid for all values of $ε$ and for energy conserving interactions. We study decoherence and markovianity properties. Our main finding is that the spin decoherence is enhanced (full decoherence) when the spin is coupled to quantum reservoir states while it is dampened (partial decoherence) when coupled to classical reservoir states. The markovianity properties depend in a subtle way on the classicality parameter $ε$ and on the finer details of the spin-reservoir interaction. We further examine scattering and periodicity properties for energy exchange interactions.